Side effects of mercury in dental amalgam - Titiek Berniyanti; Ninuk Hariyani (Dental Journal (Majalah Kedokteran Gigi), 2008)
Dental amalgam is an alloy composed of mixture of approximately equal parts of elemental liquid mercury and an alloy powder. The popularity of amalgam arises from excellent long term performance, ease of use and low cost. Despite the popularity of dental amalgam as restorative material, there have been concerns regarding the potential adverse health and environmental effects arising from exposure to mercury in amalgam. They have long been believed to be of little significance as contributors to the overall body burden of mercury, because the elemental form of mercury is rapidly consumed in the setting reaction of the restoration. In 1997, 80% of dentist in Indonesia still using amalgam as an alternative material, and 60% of them treat the rest of unused amalgam carelessly. In recent years, the possible environmental and health impact caused by certain routines in dental practice has attracted attention among regulators. As part of point source reduction strategies, the discharge of mercury/amalgam-contaminated wastes has been regulated in a number of countries, even though it has been documented that by adopting appropriate mercury hygiene measures, the impact of amalgam use in dentistry is minimal. The purpose of this paper is to examine on studies that relate mercury levels in human to the presence of dental amalgams. It is concluded that even though mercury used in filling is hazardous, if normal occupational recommendations for proper mercury hygiene routines and source of reduction strategies are followed, no occupational health risk can be assumed.